A new synonym for Pristimantis luscombei (Duellman and Mendelson 1995) and the description of a new species of Pristimantis from the upper Amazon basin (Amphibia: Craugastoridae) - Ortega-Andrade, H. Mauricio; Venegas, Pablo J. (Zootaxa, 2014)
We consider Pristimantis achuar as junior synonym of P. luscombei, based on morphological and genetic evidence. Paratype specimens of P. luscombei are part of a new species, which lead to taxonomic confusion regarding the identity of P. luscombei. We describe and name this new species as Pristimantis miktos sp. nov. from Juyuintza, Pastaza province, eastern lowlands of Ecuador. Morphological diagnostic characters used to distinguish the new species from other brownish Amazonian Pristimantis are: (1) skin of dorsum shagreen with scattered tubercles or pustules; (2) tympanum prominent; (3) a thick X-shaped scapular dermal ridge in males; and (4) an orange iris in life. Pristimantis miktos is an inhabitant of the lowlands forests of the Pastaza and Napo drainages in eastern Ecuador and northern Loreto in Peru, reaching elevations of up to 350 m; P. luscombei is widely distributed in the upper Amazon Basin of Ecuador, northern Peru and extreme western Brazil, up to 1000 m. Phylogenetic analyses reveals that P. luscombei and the new species are not closest relatives, as also deduced from morphological evidence.